Increasing Community Awareness of Sidamukti Village Community Through Waste Literacy - Sumiyarti Sumiyarti; Ida Busneti; Rinaldi Rustam; Husna Leila Yusran (Jurnal IPTEK Bagi Masyarakat, 2026)
Sidamukti Village in Sukaresmi District, Pandeglang Regency, still faces challenges in waste management. Poorly managed waste has the potential to disrupt the sustainability of residents’ livelihoods. Low levels of waste literacy and community participation are considered the main causes of this problem. This Community Service (PkM) activity aims to increase residents’ knowledge and awareness in managing waste and maintaining environmental sustainability. Using the Participatory Action Research (PAR) method, the community was actively involved in every stage, starting from problem identification, planning, to the implementation of concrete actions. Waste literacy activities were conducted through socialization programs and beach clean-up actions as participatory learning activities involving community leaders, PKK members, youth organizations (Karang Taruna), and local residents. The results show that this approach successfully improved community perceptions and behaviors toward the environment. However, to maintain the consistency of these behavioral changes, adequate waste management facilities and continuous education are required, particularly for younger generations and school children.